EVALUASI DAN MONITORING SEBAGAI SALAH SATU LANGKAH ELABORASI RENCANA PENDIDIKAN - Suparmi; Hartini, Tri; Majid, Abdul; Sulistiyana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Educational planning is a systematic process aimed at achieving educational goals effectively and efficiently. One of the key steps in elaborating an educational plan is the implementation of evaluation and monitoring. This study aims to examine the strategic role of evaluation and monitoring in supporting the success of educational planning, particularly in the context of the dynamic needs of learners and the demands of changing times. This research employs a descriptive qualitative method with a literature review approach as the primary technique for data collection. Data sources were obtained from books, scientific journals, research reports, and policy documents relevant to the topic. The analysis technique used is content analysis, by categorizing data based on key themes such as the concept of educational evaluation, the function of monitoring, and their contributions to educational planning. The findings indicate that evaluation and monitoring serve dual functions, namely as tools for quality control and as the basis for decision-making in continuous improvement. Both enable educational institutions to adjust planning strategies based on empirical data and reflections on program implementation. Evaluation helps assess the effectiveness of the plan, while monitoring ensures that implementation aligns with its objectives. The integration of evaluation and monitoring into the planning process also promotes accountability, transparency, and ongoing development. This study recommends that every educational institution establish a structured, participatory, and adaptive evaluation and monitoring system to produce more relevant and high-quality educational plans.